PERFORMANCE FACTORS OF REGIONAL OFFICE EMPLOYEES OF THE DIRECTORATE GENERAL OF TAXES CENTRAL JAVA II - Rahmat Tri Hidayat; supawi pawenang; istiatin istiatin (University of Islam Malang, 2021)
The goal of this study Is to: (1) Analyze the development ofhuman resources on the performance of employees of the Regional Officeof DJP Central Java II, (2) Analyze the influence of personal competenceon the performance of employees of the Regional Office of DJP CentralJava II, (3) Analyze the influence of work professionalism on theperformance of employees of the Regional Office of DJP Central Java II,(4) Analyze the effect of remuneration on the performance of employeesoffice Directorate General of Taxes of Central Java II, and (5) To analyzethe influence of integrity on the performance of employees of the RegionalOffice of DJP Central Java II. This type of quantitative research. Thepopulation in this study was all employees in the The Central Java IIRegional Office of the Directorate General Of Taxes,, which amounted to152 with a sample of 76 people. The sampling approach used in this studyis random sampling. Data retrieval techniques using questionnaires. Dataanalysis techniques are traditional assumption tests and multiple linearregressions. The results showed that (1) Hr development variables haveno significant effect on employee performance, (2) Personal competencyvariables have a positive and significant influence on employeeperformance, (3) Occupational professionalism variables have a positiveand significant influence on employee performance (4) Remunerationvariables have a positive and significant influence on employeeperformance, (5) Integrity variables have a positive and significantinfluence on performance official.